Markov Chain Method in Decision Implementation of Preventive Maintenance Scheduling to Reduce Equipment Downtime in PT. ADF Indonesia: Case Study - Trimarjoko, Aris; Romadhon, Ari Sulung Kurniawan (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
PT. ADF is a company operating in the shoe manufacturing industry located in Indonesia. PT. ADF has the problem of machine downtime which is currently still relatively high and requires quite a long repair time. The aim of this research is to reduce the high downtime of equipment or machines with the Markov chain method approach used in selecting the next strategy to produce a better probability of implementing scheduled preventive maintenance (PM) compared to Corrective Maintenance (CM), so that implementing a maintenance schedule is chosen to reduce downtime. equipment/machines. This strategy can reduce obstacles or disruption to production schedules. Based on the Pareto diagram, it is known that the largest downtime is caused by damage to the Rotary injection molding machine and molding machine at 80%. After implementing the preventive maintenance scheduling system as intended, the effectiveness of implementing preventive maintenance can be determined by knowing the results of calculating downtime data on Rotary printing machines and printing machines which were previously 2180 minutes/3 months to 729 minutes/3 months or the equivalent of a cost reduction of IDR. 54,735,613.00 to IDR. 18,303,790.00 or the company obtains savings of 66.56%.